Comparison between the response in air and in water of two ionization chambers exposed to low-energy X-rays - Adriana Moreno-Ramírez; Guerda Massilion (Brazilian Journal of Radiation Sciences)
This work investigated the effect of two different media in the response of two Farmer-type ionization chambers exposed to low-energy x-rays from 27 kV – 155 kV.  The measurements were performed in air and in liquid water. Independent of the ionization chamber, at effective energies below 30 keV (80 kV), the charge collected in liquid water can be up to 84% less than that generated in air. The lower is the energy, the smaller is the response in water compared to air. This can be associated to the rapid attenuation of the low-energy photon fluence by the water depth. At effective energies greater than 30 keV, the response in water becomes larger than that in air, reaching a maximum of 27% and 35% at 65 keV (150 kV) for A19 and A12 chamber, respectively. The difference in response between the two media is consistently greater for ionization chamber A19 at energy above 25 keV.